THE DEVELOPMENT DESIGN OF DIGITAL TEACHING MATERIALS ASSISTED BY POWTOON APPLICATION FOR SCIENCE LEARNING IN PRIMARY SCHOOL - Ratna Dewi; Ira Asyura; Aan Subhan Pamungkas (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
The success of a learning program is marked by the achievement of competence by students. One component that can assist teachers in conveying concepts and helping students achieve these competencies is learning media. Learning media is a channel used by teachers to convey messages so that students are motivated to learn and make it easier to understand certain concepts. Current learning media in accordance with technological developments have changed from printed to digital. One example of a teaching material capable of conveying a picture or sound message is video. Learning videos have the advantage of being able to display real examples. However, conditions in the field indicate that the use of video in schools, especially in elementary schools, has not been widely used. This is due to several factors, including the ability of teachers to produce instructional videos. Based on these findings, the purpose of this study is to develop a digital teaching material design in the form of learning videos using the powtoon application and improve students' understanding. The development model that will be used in this research is the 4D model, namely Define, Design, Develop, Disseminate. The subjects of this study were fourth grade students in one of the public elementary schools in Pandeglang Regency. The results of this study are digital teaching materials, namely learning videos designed using the help of the powtoon application on the topic of the properties of light with a very good category and understanding the concepts of students related to the concept of light properties with the quality of achievement in the good category, namely 70.30%.